(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes the state of entrepreneurship in Turkestan during the colonial period of the Russian Empire, the transformation of local merchants into owners of industrial enterprises, their incomes and activities. It was also stated that despite the opposition of the Russian government, the entrepreneurial class is firmly established in the country.